Robotics a project-based approach - Prayaga, Lakshmi; Prayagai, Chandra; Whiteside, Alex; Suri, Ramakrishna (Cengage Learning, 2015)
Have you ever thought of building your own robot? With today's technology, it's easy (and inexpensive!) to get started in this fascinating hobby. With the projects in this book and just a little bit of programming knowledge, you can create fun, functional robots.